How do patients score cosmesis after laparoscopic natural orifice specimen extraction colectomy?. (June 2015) - Wolthuis, A. M.; Meuleman, C.; Tomassetti, C.; D'Hooghe, T.; Fieuws, S.; de Buck van Overstraeten, A.; D'Hoore, A.
Abstract Aim Laparoscopic colorectal resection results in improved cosmetic outcome and better presumed body image. Laparoscopic NOSE colectomy omits an incision for specimen extraction and is supposed to further improve postoperative cosmesis. This study aimed to assess the cosmetic benefit. Method Forty‐nine patients who underwent a NOSE colectomy for bowel endometriosis from September 2009 to September 2013 were matched for age, American Society of Anesthesiologists (ASA) grade and body mass index (BMI) with patients who underwent a conventional laparoscopic colectomy for the same indication. Patients were asked to complete a questionnaire consisting of a body scale and a cosmetic scale and the Patient Scar Assessment Questionnaire (PSAQ) including five subscales (appearance, symptoms, scar consciousness, satisfaction with appearance and satisfaction with symptoms). Results Patient demographics were similar between both groups. Patients were assessed at a median postoperative follow‐up of 41 months in the NOSE colectomy group and 35 months in the conventional resection group. The median body image questionnaire score was 15 for NOSE colectomy and 18 for conventional resection (P = 0.027). The respective median PSAQ scores were 56 and 71 (P = 0.002). There was a good relationship between the PSAQ score and the body image questionnaire (Spearman correlation coefficient 0.82). Conclusion Depending on the scoring system used, the cosmetic outcome may be better after NOSE colectomy than conventional laparoscopy in patients having surgery for endometriosis. The comprehensive body image questionnaire, being shorter and easier to use, could be a valid tool for assessing cosmesis after NOSE procedures.